The effect of anesthesia on postoperative cognitive dysfunction in adults undergoing cataract surgery: a systematic review - Elaheh Foroughi; Etrusca Brogi; Francesco Forfori; Seyyed Taghi Hashemi (BMC Anesthesiology)
Abstract Background We systematically reviewed the evidence on the effect of anesthetic methods and drugs on the incidence of postoperative cognitive dysfunction (POCD) after cataract surgery. Methods The Web of Science, PubMed, and Scopus databases were searched for relevant English reports published from 2000 to August 2024. After full-text screening and checking the quality assessment of each article using the JBI checklist, 9 relevant articles were included in this study. The included articles were reviewed to explain how different anesthetic modalities and drugs may affect the incidence of POCD after cataract surgery. Our study aimed to systematically investigate the relationship between various methods of anesthesia and POCD for people undergoing cataract surgery. Results We included 9 clinical trials with 1014 participants, which analyzed the incidence of POCD after anesthetic interventions. Four articles compared the effect of anesthetic modality interventions on POCD and five studies compared the effect of anesthetic drugs on POCD. The studies used various cognitive measurement scales, including the Mini-Mental State Examination, Neurobehavioral Rating Scale, Blessed Orientation-Memory-Concentration Test, Iowa Satisfaction with Anesthesia scale, PALT, and VF test. All articles that compared local and topical anesthesia found no statistically significant difference in the incidence of cognitive dysfunction at postop days 1 and 7. General anesthesia may cause POCD approximately twofold than local anesthesia. Ketamine, Midazolam, or Dexmedetomidine seemed to reduce postoperative cognitive complications compared to the control group‌‌. Conclusions This systematic review investigates how different anesthetic techniques and drugs may affect the incidence of POCD. The available literature is far from being conclusive and further studies are needed to reach any significant conclusions. It is necessary to adopt an appropriate anesthesia method for elderly and high-risk patients, especially people who have a history of cognitive problems‌‌ undergoing elective cataract surgery, to reduce cognitive complications after surgery.‌